Ecologia de invertebrados aquáticos em riachos de altitude do planalto de Poços de Caldas, MG, Brasil - Santos, Mireile Reis dos (2018)
Streams are unique and isolated environments that include a wide range of species. These species have close relations with these ecosystems and may have different patterns of ecological responses. Thus, this study compared the communities of aquatic invertebrates of twenty-six (26) first to third order streams of three watersheds in a high-altitude region with different soil uses, chiefly eucalyptus plantations. Furthermore, investigated which component (space or environmental) and approach were decisive in the structuring of these metacommunities and relates them to the functional evolutionary traits of different taxonomic groups. A limnological comparison was made of the streams and watersheds using permutational multivariate analysis of variance (PERMANOVA). The structure of the communities was compared based on richness, abundance, and diversity (alpha and beta) and some metrics to determine environmental quality. The biological composition was compared by means of exclusive and shared taxa and frequencies of occurrence and dominance them. Was applied a Partial Redundancy Analysis – RDA- partial to verify the proportion of explicability of the environmental and spatial components. Limnological differences were detected between the three watersheds themselves and the streams in the watersheds. Richness and abundance accompanied the decreasing pattern for the watersheds from the best to the worst environmental quality and highlighted the differences between the watersheds in comparisonto the diversity indices. In general and in all three watersheds, most of the identified taxa were rare. Among the indicator taxa, the more sensitive clades had a higher probability of occurrence in the more preserved locations, while the more tolerant clades were more likely to occur in more impacted environments. The studied communities were less influenced by the spatial component and the environmental component was crucial to all taxonomic groups, albeit individually for each taxon. Both components correlated with the selected functional traits. In the studied region, changes to the landscape, especially resulting from the introduction of eucalyptus and the lack of conservation practices, can determine the elimination of resident aquatic invertebrates.